"An island of excellence"? How the Pakistan military reflects on its presence in the development sector - Rabia Chaudhry (University of Bonn, Center for Development Research (ZEF), 2019)
In addition to defending their countries, modern day militaries assist the state in labour intensive non-defence related activities. These range from disaster relief to providing administrative assistance. In countries where the military already exercises hegemonic control, possession of such auxiliary capabilities can potentially provide an avenue to extend the military's jurisdiction and further strengthen its hegemony. This paper is based on a chapter of doctoral dissertation titled An Army with a Country: How the Pakistan military imposes hegemony via the infrastructure and welfare sectors. The thesis discusses how the Pakistan military reproduces and reinforces its hegemony through its presence in the development sector. This paper concentrates on one particular aspect thereof - that is, the elements within the military mind-set that inform its modus operandi. How the Pakistan military operationalises its presence in the development sector to further consolidate its hegemony needs scrutiny. This paper concentrates on the considerations and the surrounding thought processes that compel the military to play an active developmental role - to which it refers to as nation building. Using primary data in the form of semi structured interviews of serving and retired senior military officers, this paper shows how the military defines its self-interests, reflects upon its own developmental role and, which avenues it selects to pursue.
Keywords: 330; Hegemony; military; shared mental models; development; nation building